2015
DOI: 10.1007/s00198-015-3283-y
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal balance of the spine in patients with osteoporotic vertebral fractures

Abstract: Global spinal balance is abnormal in subjects consulting for osteoporosis, even in subjects without VFs. VFs and age are determinants of abnormal sagittal global balance; however, pelvic parameters play a role in compensatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…In our previous study, T1 sagittal angle, together with age and PT, was found to be one of the three primary contributors to maintaining sagittal balance. As pelvic parameters play a role in compensatory mechanisms [ 25 ], finding out the possible factors for T1 sagittal angle might be as equally important as finding out the predictors for the whole sagittal balance. In addition, our previous study [ 12 , 13 ] also found that LL and TK were important contributors to sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, T1 sagittal angle, together with age and PT, was found to be one of the three primary contributors to maintaining sagittal balance. As pelvic parameters play a role in compensatory mechanisms [ 25 ], finding out the possible factors for T1 sagittal angle might be as equally important as finding out the predictors for the whole sagittal balance. In addition, our previous study [ 12 , 13 ] also found that LL and TK were important contributors to sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited studies have investigated the effect of exercises as an intervention for hyperkyphosis on physical function, balance and the quality of life among the elderly, especially elderly men. In most studies, only the effect of corrective training on the severity of hyperkyphosis has been evaluated [9][10][11][12][13]. Thus, the impact of training programs on the complications of hyperkyphosis has received little attention.…”
Section: Objectivesmentioning
confidence: 99%
“…In osteoporotic patients, the abnormal bone mass can affect the mechanical properties of the bone (23) and may lead to low back pain, disc degeneration or wedge fracture of the vertebral body (45678). Moreover, the decreased bone mass of the cervical vertebrae is closely related to loosening of the spinal surgical implant screws and the artificial inter-vertebral disc substitutes (910).…”
Section: Introductionmentioning
confidence: 99%